Effect of immunosuppressive therapy on patients with inflammatory bowel diseases and hepatitis B or C virus infection. Issue 3 (30th July 2012) - Morisco, F.; Castiglione, F.; Rispo, A.; Stroffolini, T.; Sansone, S.; Vitale, R.; Guarino, M.; Biancone, L.; Caruso, A.; D'Inca, R.; Marmo, R.; Orlando, A.; et al.
Summary Viral hepatitis reactivation has been widely reported in patients undergoing immunosuppressive therapy; however, few data are available about the risk of HBV and HCV reactivation in patients with inflammatory bowel disease, receiving immunosuppressive drugs. The aim of our study was to assess the prevalence of HBV and HCV infection in a consecutive series of patients with inflammatory bowel disease and to value the effects of immunosuppressive therapy during the course of the infection. Retrospective observational multicenter study included all consecutive patients with inflammatory bowel disease who have attended seven Italian tertiary referral hospitals in the last decade. A total of 5096 patients were consecutively included: 2485 Crohn's disease and 2611 Ulcerative Colitis. 30.5% and 29.7% of the patients were investigated for HBV and HCV infection. A total of 30 HBsAg positive, 17 isolated anti‐HBc and 60 anti‐HCV‐positive patients were identified. In all, 20 patients with HBV or HCV infection received immunosuppressive therapy (six HBsAg+; four isolated anti‐HBc+ and 10 anti‐HCV+). One of six patients showed HBsAg+ and one of four isolated anti‐HBc+ experienced reactivation of hepatitis. Two of six HBsAg patients received prophylactic therapy with lamivudine. Only one of 10 anti‐HCV+ patients showed mild increase in viral load and ALT elevation. Screening procedures for HBV and HCV infection at diagnosis have been underused in patients with inflammatory bowel disease. We confirm the role of immunosuppressive therapy in HBV reactivation, but the impact on clinical course seems to be less relevant than previous reported.